2002
DOI: 10.1046/j.1365-2257.2002.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Low cost autologous peripheral blood stem cell transplantation performed in a municipal hospital for a patient with plasma cell leukaemia

Abstract: Autologous peripheral blood stem cell transplantation (PBSCT) is a costly procedure. In India, the cost varies from US$20000 to 25000 and most patients cannot afford it. Using several cost-cutting measures, we were able to treat a patient with plasma cell leukaemia by autologous PBSCT. A 42-year-old-male presented with plasma cell leukaemia. He was treated with VAD therapy, followed by high-dose cyclophosphamide and granulocyte colony-stimulating factor (G-CSF) for mobilization of peripheral blood stem cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The presence of p53 deletion, 13q deletions, karyotypic complexity, hypodiploidy and 1q gains could confer an advanced stage on PC disease progression characterized by therapy resistance and a dismal prognosis [17]. There are older sporadic reports from India of treatment of primary PCL with single agent ifosfamide [18] and more recent reports of autologous stem cell transplantation in patients with pPCL who relapsed after initial remission [19,20]. Unlike MM, survival with PCL has not improved over time.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of p53 deletion, 13q deletions, karyotypic complexity, hypodiploidy and 1q gains could confer an advanced stage on PC disease progression characterized by therapy resistance and a dismal prognosis [17]. There are older sporadic reports from India of treatment of primary PCL with single agent ifosfamide [18] and more recent reports of autologous stem cell transplantation in patients with pPCL who relapsed after initial remission [19,20]. Unlike MM, survival with PCL has not improved over time.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this analysis, the cost related to the hematopoietic stimulating factor was excluded. In a recent study, Ghosh et al (2002) reported that the PBSC cost for a patient with plasma cell leukemia was US$20 000-25 000. The major part of the costs was related to hospitalization, growth factors, blood products, collection and cryopreservation of PBSC.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this analysis, the cost related to the hematopoietic stimulating factor was excluded. In a recent study, Ghosh et al. (2002) reported that the PBSC cost for a patient with plasma cell leukemia was US$20 000–25 000.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Ghosh et al [40] reported a PBSCT cost for patients with plasma cell leukemia that ranged from US$ 20000 to US$ 25000. The major part of the costs related to hospitalization, growth factors, blood products, collection and cryopreservation of PBSC.…”
Section: Cost Analysismentioning
confidence: 99%